Africa: «The Rainbow Period» and Unfulfilled Hopes. Interview with Apollon Davidson, Academician of RAS - D. A. Degterev; V. I. Yurtaev (Vestnik RUDN. International Relations, 2020)
Academician Apollon B. Davidson is an outstanding Soviet and Russian expert in African history, British Studies, also known as a specialist in Russian Silver Age literature. He is an author of more than 500 scientific papers, including 11 monographs, most of which are devoted to the new and recent history of the countries of Tropical and South Africa. Graduate of Leningrad State University (1953), Professor (1973), Doctor of Historical Sciences (1971), Academician of the Russian Academy of Sciences (2011). Under his leadership, at the Institute of World History of the Russian Academy of Sciences a scientific school of African history based on archival documents was created. He prepared more than 30 candidates and doctors of sciences, among famous students - A. Balezin, S. Mazov, I. Filatova, G. Derlugyan. In 2001-2002 two volumes of documents “Russia and Africa” [Davidson 1999] were published under his editorship; the book “USSR and Africa” [Davidson, Mazov, Tsypkin 2002], in 2003 - the volume of documents “Comintern and Africa” [Davidson 2003]. In 2003, a two-volume edition of the documents “South Africa and the Communist International” [Davidson, Filatova, Gorodnov, Johns 2003] was published in London in English, and in 2005-2006 - the fundamental three-volume “History of Africa in Documents” [Davidson 2005-2006]. In 1988, he participated in the South African program at Yale University. In 1991, he lectured for several months at universities in South Africa and worked in the archives of this country. In 1992-1993 he worked at the Rhodes University, in 1994-1998 organized and chaired the Center for Russian Studies at the University of Cape Town. In 1981-1991 he visited Ethiopia, Angola, Lesotho, Botswana and several times - Mozambique, Zambia, Zimbabwe and South Africa. From 1977 to 1991 he participated in the Soviet-American Dartmouth conferences as an expert on Africa. In his interview he talks about the outcome of decolonization for southern Africa, the actual problems of the modern development of the continent, the role of China in Africa, and the Afro-Asianization of the world. Special attention is paid to the problems and prospects of the development of Soviet and Russian African studies and Russian-African relations.